Digital adaptation and educational support : challenges of low-income families in Singapore during the COVID-19 pandemic - Tay, Mei Ling (Nanyang Technological University, 2021)
This paper studies the impact of Covid-19 on the ability of lower-income families in Singapore to navigate and adapt to digital transformation in education. Through qualitative interviews with 10 parents and 4 organisations, it will focus on the challenges and practices pertaining to how parents supported their children in home-based learning (HBL) during the CB period, between early April to May 2020. We also conduct a comparison with middle-income and higher-income households to investigate how parents mobilised their resources and prioritised their commitments differently. Specifically, we argue that social class is an integral factor in mediating this whole experience. We saw that classic divisions along education and socio-economic status translated to digital disparities not only in access to digital devices, but trickle down deeper to shape parents and children’s capabilities in terms of their differentiated ability to fully harness technology for an effective HBL experience.